TECHNOLOGIES FOR ENSURING EFFECTIVE MARKETING ACTIVITIES OF INDUSTRIAL ENTERPRISES - KALMANOVYCH, OLEKSANDR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the conditions of strengthening of integration and globalization processes, frequent changes of conditions of functioning the industrial enterprises need to create adaptation mechanisms, to improve system of management of financial and economic activity, to define directions of increase of competitiveness of production and prospects of expansion of markets, and also to improve marketing activity. Making changes in the processes of marketing research, the formation of marketing strategies, market segmentation with consideration of issues regarding product positioning will increase the level of marketing efficiency in the enterprise. Only with the improvement of technologies to ensure effective marketing activities for the company it becomes possible to expand market segments, constantly monitor changes in consumer preferences (needs), as well as trends in doing business in a particular segment of sales and more. The article examines the essence of marketing and marketing activities of the enterprise. It is determined that the improvement of marketing activities, namely marketing technologies at the enterprise is an urgent task due to the growing role of marketing activities and its impact on the results of the enterprise. The interdependence of management functions and management functions of marketing activity of an industrial enterprise is proved. The role of such components of the management system as control and analysis in improving the efficiency of marketing activities of the business entity is proved. The basic directions of improvement of marketing activity of the industrial enterprise, in particular in marketing researches, in a price policy, at product development, in advertising activity, in organizational structure and in the organization of distribution of the goods are allocated. The influence of the formed marketing strategy on the achievement of the set current and strategic goals of doing business is substantiated. The basic concepts of marketing on the basis of which the company manages marketing activities are considered. The influence of the organization of the marketing structure (marketing department) and the corresponding information support on the effectiveness of marketing activities and obtaining the goals of the enterprise is studied. The necessity of forming a system of indicators according to which the management staff will be able to assess the level of efficiency of marketing activities of an industrial enterprise is proved.